2011
DOI: 10.1016/j.jpag.2011.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Intention to Vaccinate a Daughter against HPV: A Statewide Survey in Alabama

Abstract: Purpose-Human papillomavirus (HPV) is the most common sexually transmitted infection in the United States. Adolescent and young adults aged 15-24 were estimated to account for three quarters of new infections in 2000. Two HPV vaccines are currently available. The vaccine is recommended for girls aged 11-12 years. Previous research has indicated that African-American and Asian-American parents are less likely to vaccinate their daughters than Caucasians. This investigation examines the relationship between demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 24 publications
5
36
0
Order By: Relevance
“…This study provides a clinical validation and extends our understanding of numerous surveys reporting that most young women did not plan to modify their sexual behaviors after HPV vaccination. 15,[19][20][21][22][23][24][25] Although most previous surveys have been cross-sectional, a recent longitudinal survey conducted in the United Kingdom documented no difference in the proportion of women reporting initiation of sexual activity after HPV vaccination 30 ; however, that study was conducted in women aged 16 to 18, of whom 37% had already become sexually active. 30 In our analysis, HPV vaccination at ages 11 through 12 did not increase the likelihood of seeking medical attention for outcomes related to sexual activity with up to 3 years of follow-up.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This study provides a clinical validation and extends our understanding of numerous surveys reporting that most young women did not plan to modify their sexual behaviors after HPV vaccination. 15,[19][20][21][22][23][24][25] Although most previous surveys have been cross-sectional, a recent longitudinal survey conducted in the United Kingdom documented no difference in the proportion of women reporting initiation of sexual activity after HPV vaccination 30 ; however, that study was conducted in women aged 16 to 18, of whom 37% had already become sexually active. 30 In our analysis, HPV vaccination at ages 11 through 12 did not increase the likelihood of seeking medical attention for outcomes related to sexual activity with up to 3 years of follow-up.…”
Section: Discussionmentioning
confidence: 94%
“…[13][14][15][16][17][18] Most teenage girls surveyed on knowledge, attitudes, and practices related to HPV vaccination reported they would not modify their sexual behaviors after HPV vaccination. 15,[19][20][21][22][23][24][25] Most of these studies were limited by the use of selfreported, cross-sectional surveys, 15,[19][20][21][22][23][24][25] however, and it is unknown if these survey results would directly translate to clinical outcomes.…”
mentioning
confidence: 99%
“…Physician recommendation is the most effective indicator of HPV vaccine uptake among young adult women, and this fact is well established. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] This study showed the potential of using the ED for initiating HPV vaccine uptake and series completion among young women who otherwise would not have health care access for this important preventive intervention.…”
Section: Discussionmentioning
confidence: 73%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Preventive care, specifically HPV vaccination, for females are traditionally driven by Pediatricians, Family Physicians, and Obstetricians/ Gynecologist (OB/GYN). 1 Professional organizations in these specialties consistently support HPV vaccine uptake; yet, vaccine recommendation rates vary by provider specialty.…”
Section: Introductionmentioning
confidence: 99%
“…Perceived barriers to vaccination can contribute to a lack of provider recommendation, missed opportunities for vaccination, and low rates of vaccination coverage among adolescents [14][15][16]. The barriers are categorized and discussed as follows: knowledge, vaccine safety, cultural, policy, cost, and structural barriers to vaccine [17,18].…”
Section: Perceived Barriers To Vaccination Among Providersmentioning
confidence: 99%